Factores de riesgo y su relación con la prevalencia de partos prematuros. Hospital IESS Babahoyo, periodo octubre 2024 - mayo 2025. - Pumadera Flores, Johanna Isabel (2024)
Premature birth is one of the main causes of neonatal mortality in Ecuador, especially in areas with limited access to health services. The study aimed to determine the risk factors associated with the prevalence of preterm births at the IESS Babahoyo Hospital during the period from October 2024 to May 2025. A combination of qualitative and quantitative approaches was executed through descriptive and analytical methods, collecting information from 90 pregnant women through surveys and analysis of medical records. Adverse socioeconomic conditions such as family income and difficulty in accessing health services, pre-existing medical conditions such as hypertension, low weight and urinary/vaginal infections, previous miscarriages, the presence of complications in previous pregnancies, and the use of substances such as alcohol and tobacco were found to be key determinants of prematurity. Among the most common neonatal complications were respiratory distress syndrome and sepsis. Mothers who have experienced multiple pregnancies or miscarriages are more susceptible to complications in future pregnancies. In conclusion, it is necessary to improve the quality of prenatal care, optimize hospital infrastructure and establish emotional and educational support programs for pregnant women. Jointly, preventive strategies such as the control of comorbidities and preconception counseling are suggested, along with the promotion of future research that comprehensively addresses this problem.